Synthesis, thermal degradation and dielectric properties of poly[2-hydroxy,3-(1-naphthyloxy)propyl methacrylate] - Biryan, Fatih; Demirelli, Kadir; Torgut, Gulben; Pihtili, Guzin (Springer, 2017)
2-Hydroxy-3-(1-naphthyloxy)propyl methacrylate (NOPMA) monomer was synthesized from reaction of 2-[(2-naphthyloxy)methyl]oxirane with methacrylic acid in the presence of pyridine. The polymerization of NOPMA was carried out by free radical polymerization method in the presence of AIBN at 60 A degrees C. The structure of monomer and polymer was characterized by H-1-NMR, C-13-NMR and FT-IR spectroscopy techniques. The glass transition temperature and average-molecular weights of poly(NOPMA) were measured using differential scanning calorimetry and gel permeation chromatography, respectively. The thermal degradation behavior of poly(NOPMA) has been investigated by FT-IR studies of the partially degraded polymer and thermogravimetry. The cold ring fractions (CRFs) were collected at two different temperatures, initially fraction-1 (CRF1) is from room temperature to 320 A degrees C, and the other fraction-2 (CRF2) is from 320 to 500 A degrees C. The volatile products of the degradation were trapped at -195 A degrees C (in liquid nitrogen). All the fractions were characterized by FT-IR, H-1 and C-13-NMR spectroscopic techniques, and the cold ring fractions (CRFs) were also characterized by GC-MS. For the degradation of polymer, the major compound between products of CRFs is alpha-naphthol. The GC-MS, FT-IR and NMR data showed that depolymerization corresponding to monomer was not prominent below 320 A degrees C in the thermal degradation of poly(NOPMA). The mode of thermal degradation containing formation of the major products was identified. The dielectric permittivity (epsilon'), the loss factor (epsilon aEuro(3)) and conductivity (sigma(ac)) were measured using a dielectric analyzer in the frequency range of 50 Hz to 20 kHz.
Keywords: NOPMA synthesis; Thermal degradation; Dielectric properties; Polymerization